Penerapan Data Mining Analisa Data Penjualan Obat Menggunakan Metode Random Forest - Reka, Cut (Bulletin of Data Science, 2022)
Data Mining is a method used to find and explore certain hidden data from big data. For example, data mining can be used to find information on the combination of items in a sale. By using data mining, companies will be able to analyze precisely, quickly and accurately compared to analyzing manually. The pharmacy is one of the companies that can take advantage of this data mining method, because in the pharmacy sales transactions take place every day so that the longer the sales data stored is very large. Application of Data Mining sales data analysis Using the Random Forest Method in this method the data and attributes are taken at random so that it is possible to produce a decision tree model, the benefits of which are to facilitate the analysis of large data and help provide information on processed sales data.